Linking e-hrm practices and organizational outcomes: empirical analysis of line manager’s perception - Iqbal, Naveed; Ahmad, Mansoor; Raziq, Muhammad Mustafa; Borini, Felipe Mendes (Review of Business Management, 2018)
Purpose - This study seeks to explore the value creation opportunities offered by e-HRM practices. The purpose of this paper is to examine the impact of operational, relational, and transformational e-HRM practices on organizational outcomes by incorporating HRM service quality as an intermediary value creating factor. Design/methodology/approach –Line managers of commercial banks that adopted operational, relational, and transformational e-HRM were asked to participate in the study. The study used exploratory factor analysis for scale validation. PLS-SEM was used to validate and test the conceptual model. Findings - Drawing on data from a large and new survey, the study found that operational, relational, and transformational e-HRM practices have a significant impact on HR service quality and employee productivity. HRM service quality mediates the relationship between e-HRM practices and organizational outcomes. Implications - The study focuses on the relevance of e-HRM practices for improving organizational effectiveness, leading to competitive advantage for the firm. It is one of the pioneering studies that explore the link between e-HRM practices and organizational outcomes by analyzing the perception of South Asian line managers from the banking sector. Organizations from developing and developed countries can extract benefits by designing and implementing e-HRM systems in a way that supports their workflow.